2004
DOI: 10.1038/sj.leu.2403418
|View full text |Cite
|
Sign up to set email alerts
|

An update: 12-year follow-up of patients with hairy cell leukemia following treatment with 2-chlorodeoxyadenosine

Abstract: Long-term results of both pretreated and previously untreated patients (pts) with hairy cell leukemia (HCL) using uniformly a single 7-day course of 2-chlorodeoxyadenosine (2-CdA) by continuous infusion are reported. In addition, the probability of obtaining another response with this drug in pts who relapsed after 2-CdA treatment will be addressed. A total of 44 consecutive pts (34 males, 10 females) with a median age of 57 years (range 33-77) at the time of initiation of 2-CdA treatment were analyzed. In all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
61
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 24 publications
(25 reference statements)
13
61
2
2
Order By: Relevance
“…At the University of Munich, extended results were reported by Jehn et al 16 in 44 patients with a median follow-up of 8.5 years. All except 1 individual (98%) achieved a CR, defined as normalized peripheral blood cell counts, no morphologic evidence of HCL in the bone marrow, and lack of measurable disease.…”
Section: Long-term Resultssupporting
confidence: 58%
“…At the University of Munich, extended results were reported by Jehn et al 16 in 44 patients with a median follow-up of 8.5 years. All except 1 individual (98%) achieved a CR, defined as normalized peripheral blood cell counts, no morphologic evidence of HCL in the bone marrow, and lack of measurable disease.…”
Section: Long-term Resultssupporting
confidence: 58%
“…[14][15][16][17] Northwestern University has reported similar outcomes, with an OS rate of 87% at 12 years in HCL patients receiving a single course of cladribine. 17 In this report, 88 HCL patients were #40 years of age at diagnosis, with a median age of 36 years.…”
Section: Discussionmentioning
confidence: 68%
“…8,[11][12][13][14]16,[18][19][20] After relapse, treatment with an additional course of purine analogues is recommended. It is acceptable to repeat the same treatment that was given initially, although changing to a different purine analogue will yield the same results.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Treatment with 2-chlorodeoxyadenosine or 2 0 -deoxycoformycin resulted in 80% to 90% CR, with a relapse rate of 25% to 30% at 3-to 5-year follow-up. 7 In past years, several reports [8][9][10][11][12][13][14] of long-term follow-up studies with a single purine analogue have confirmed that the overall CR rates are very similar, ranging from 76% to 98%, and the relapse rates are equally comparable, showing that about 30% to 40% of patients would relapse after 5 to 10 years of follow-up. These reports indicate that both purine analogues are highly effective and lead to excellent overall survival; however, it appears that neither purine analogue is likely curative, because molecular studies suggest that all patients have evidence of minimal residual disease while in CR.…”
mentioning
confidence: 99%